Study on anxiety, depression, and sleep conditions and their interrelations among vocational college students during the COVID-19 pandemic management normalization - Gao, Ru; Wang, Hailian; Liu, Shan; Wang, Xia; Song, Siyuan; Wang, Yi (Frontiers in Public Health, 2024)
ObjectiveThis study investigates the sleep patterns among vocational college students and examines their association with anxiety and depression amidst the ongoing normalization of COVID-19 management strategies.MethodsIn the period of January to February 2022, a comprehensive survey was conducted involving a random sample of 3,300 students. By employing face-to-face interviews, data on general demographics, along with levels of anxiety, depression, and sleep quality, were meticulously gathered and analyzed.ResultsOut of the 3,049 questionnaires deemed valid for analysis, the prevalence rates for anxiety, depression, and insomnia were found to be 9.7, 14.1, and 81.9%, respectively. Through regression analysis, several factors were identified as significant predictors of insomnia: female gender, a self-perceived average or poor family economic status over the last year, moderate psychological stress due to the pandemic and its associated restrictions, extended daily screen time during the pandemic, absence of a routine physical exercise regime, significant disruption or alteration of daily life routines due to the pandemic, presence of anxiety and depression symptoms during the pandemic, and only partial restoration of normal life routines post-pandemic control measures (p < 0.001, p < 0.005, or p < 0.050). A strong correlation was observed among the symptoms of anxiety, depression, and insomnia (all p < 0.001). The correlation between stress and depression, depression and insomnia, and anxiety and insomnia were 0.824, 0.714, 0.620, respectively, (all p < 0.001).ConclusionGiven the substantial impact of abrupt or prolonged crisis events, it is imperative to develop and implement specific intervention strategies aimed at safeguarding the psychological well-being of college students.